Chracterization of Brazed Joints in Titaniumtostainless Steel Using (Ni-Cu-Ag_Pb) Composite Filler . (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Diffusion brazing was performed   between Stainless Steel (304L)and pure titaium using a filler  alloy (Ni-Cu-Ag-Pb) system at temerature range of (750,850,950,1050)°C for 30 minutes with a vaccum furnacepa technique. The results show that the diffusion brazing temperature is a critical Factor controlling the microstructure of specimens. The microstructure was investigated using light microscop and scanning electron microscope equipped with an energy dispersive  X- ray system(EDX). The best results of microstructure  investigation was  a chived for joint brazed at 950°C  for 30 minutes.Above this temperature at 1050°C showed  that the craks propagates noticeably wih increased temperature. The joint Sections analyzed by using SEM and Edx to observe the produced phases. The major phases of brazed joints using filler  alloy gives (α –Ni) (Ni-Cu)and (Ni-Cu-Ag)Phases